Pengelolaan Administrasi Sekolah Berbasis Mutu Studi Situs SMK Negeri 1 Depok Sleman Yogyakarta - Nafiah, Daimatun (2011)
The purpose of this study were (1). Describe the characteristics of Standard Operating Procedures (SOP) Administration School at SMK Negeri 1 Depok Sleman, Yogyakarta. (2). Describe the characteristics of Archives Administration School of Administration at SMK Negeri 1 Depok Sleman, Yogyakarta. (3). Describe the characteristics of structure and function of school organization in SMK Negeri 1 Depok Sleman, Yogyakarta. This study was conducted using qualitative. Data were collected through interviews. The research informants chosen by considering the position, functions, duties, and responsibilities of the administrative management and other relevant information. All data obtained from the field collected and processed by means of classified, selected and analyzed. The collected data is checked its validity through triangulation techniques, analyzed by the process of data reduction, data display, discussion, and conclusion. The results of this research (1). Standard Operating Procedure (SOP) has organized school administration and has been documented. Application of SOP in the range of services the school administration has been good, however it still needs to be added to correspondence service procedures. Standard Operating Procedure (SOP) covering the areas of curriculum administration, student administrative areas, administrative areas and Infrastructure, Administration, Industrial Relations field, and the Organization and Management. (2). Settlement activity of the archives has been good. However, in the case of borrowing records, be recorded on the books formatted. These activities include: record archive/mail in/out on the notebook, double letter/document as a file to be saved, save the letter/document on the basis of the problem. Placement of the archive file using a rack with an easy placement of affordable and safe. The equipment used was adequate according to need. Borrowings are recorded in the records books. Records maintenance activities carried out by cleaning and reorganization of the archives. (3). Structure and function of the organization is clearly structured. Each organization has a job description and responsibilities clearly and in writing. The organizational structure is headed by the principal. In performing its duties, assisted by the Vice Principal of Curriculum Affairs, Vice Principal of Student Affairs, Vice Principal of areas and Infrastructures Affairs, Vice Principal of Relations and Industrial Affairs, Quality Management Representative, Head of Administration and Teachers.